2001
DOI: 10.4321/s0212-71992001000400010
|View full text |Cite
|
Sign up to set email alerts
|

La homocisteína: ¿El factor de riesgo cardiovascular del próximo milenio?

Abstract: La homocisteína es un aminoácido que se sintetiza en el organismo a partir de otro: la metionina. La única fuente de metionina es la ingesta, a partir principalmente de proteínas animales. El metabolismo de la homocisteína está muy relacionado con las vitaminas B 6 , B 12 y ácido fólico. La metionina que proviene de la ingesta se metaboliza, principalmente en el hígado, en homocisteína (Figura 1). A partir de aquí, la homocisteína puede seguir dos vías: a) Remetilación: transformarse de nuevo en metionina, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
0
4
0
2
Order By: Relevance
“…The report that statins can reduce the incidence of DVT, although not in the idiopathic type (2)(3)(4), can be considered a helpful criterion for correlating the two pathologies, but it is not sufficient for the demonstration of a causal correlation of the two vascular events. In the substance, the subjects with DVT and the controls have the same incidence of IMT and of plaques.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The report that statins can reduce the incidence of DVT, although not in the idiopathic type (2)(3)(4), can be considered a helpful criterion for correlating the two pathologies, but it is not sufficient for the demonstration of a causal correlation of the two vascular events. In the substance, the subjects with DVT and the controls have the same incidence of IMT and of plaques.…”
Section: Resultsmentioning
confidence: 95%
“…Another research work evaluated the association between current use of statins and risk of idiopathic venous thromboembolism and found that the use of this drug did not reduce the risk (3). Moreover, in recent years hyperhomocysteinemia has been considered an important risk factor for atherosclerosis and it has also been correlated with an increased risk for DVT (4,5).…”
mentioning
confidence: 96%
“…Mutations in the MTHFR gene disrupt folate acid metabolism, resulting in methyltetrahydrofolate deficiency and HHcy with hypomethioninemia. Disorders related to cobalamin (cbl-) metabolism, particularly cblC, combine methylmalonic acidemia (MMA) with HCU [ 4 , 18 ]. These disorders manifest with significantly elevated Hcy levels (>50 μmol/L).…”
Section: Types Of Hyperhomocysteinemias (Hhcy)mentioning
confidence: 99%
“…Mediante el metabolismo de la Met se pueden generar metabolitos intermedios como la homocisteina y también productos como la cisteína (Cys) (Li, Yin, Li, Kim, & Wu, 2007). La síntesis de Cys mediante la Met es producto de la transulfuración, donde se genera una unión de serina a la Met (Suárez, Gómez, Ríos, Barbado, & Vázquez, 2001). Una de las funciones de la Cys es la síntesis del glutatión (GSH) (Li et al, 2007), siendo un tiol formado por tres pétidos (γ-L-glutamil-L-cisteína-glicina) (Díaz-Hung, González, & Blanco, 2015).…”
Section: Metionina Y Su Función Antioxidanteunclassified